Promotion of Au nanoparticles on carbon frameworks for alkali-free aerobic oxidation of benzyl alcohol - Du, Zhongtian; Zhang, Sen; Yang, Sihan; Yang, Wenhao; Luo, Jingjie; Liang, Changhai (Frontiers in Chemical Engineering, 2023)
We synthesized a series of modified Co-ZIF-67 materials with tunable morphology to support fine Au nanoparticles for the alkali-free aerobic oxidation of benzyl alcohol. Structure promotion was performed using Stöber silica as a hard template, which was subsequently removed by NaOH etching before gold immobilization. The texture structure of Au/(Si)C was greatly improved with increasing surface area and volume. CoOx was simultaneously introduced into the carbon shell from the Co-ZIF-67 precursor, which consequently facilitated the specific Au-support interaction via bimetallic synergy. XRD, XPS, and TEM images demonstrated the redispersion of both Au and CoOx as well as the electronic delivery between metals. Analysis of the chemical and surface composition suggested a surface rich in Auδ+ with abundant lattice oxygen contributed by CoOx in the final Au/(Si)C, which improved the transformation rate of benzyl alcohol even in an alkali-free condition. Au/(Si)C with finely dispersed Au particles showed excellent catalytic performance in the alkali-free environment, with 89.3% benzyl conversion and 74.5% benzaldehyde yield under very mild conditions.